Amphipod glycogen and glucose content under simulated invasion stress in wetlands - Richelle L Tanner; Lorna E Haworth; Sarah Nancollas; Susie N Landa; Anne E Todgham (PANGAEA, 2024)
Every two weeks during the 6-week acclimation period, 8 adults were randomly selected from each tank glycogen analysis (n = 8). Individuals were sacrificed in dry ice and stored at -80 °C. Frozen amphipods were ground into fine powder using a liquid nitrogen cooled mortar and pestle. Glucose and glycogen metabolites were extracted separately to be analyzed using a colorimetric assay. Glycogen was extracted by adding 1 ml of ice-cold 8% HClO? to approximately 20 mg of powdered amphipod tissue and then homogenized on ice for approximately 10 seconds with a Pro200 Bio-Gen Series homogenizer (PROScientific, Oxford, CT, USA). A 200 μl sample of the homogenate was frozen at -80 °C for later glycogen analysis. The remaining homogenate slurry was centrifuged at 10,000 g for 10 minutes at 4 °C and the supernatant was extracted and neutralized with 3 mol l?^1 K?CO?. The solution was centrifuged again at 10,000 g for 10 minutes at 4 °C and frozen at -80 °C for the glucose assay. Glycogen samples were enzymatically digested using previous methods (Hassid & Abraham, 1957) and analyzed for glucose following methodology (Bergmeyer, 1983) modified for microplate spectrophotometer (Synergy HT, Biotek, Winooski, VT, USA). Glycogen content was then corrected for starting glucose.
In: Tanner, RL et al. (2024): Amphipod protein, glycogen, and glucose content under simulated invasion stress in wetlands [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.973173